The Influence of Industrial Work Practice Experience-Career Information on Student Competence with Work Motivation as an Intervening Variable in Bachelor of Electrical Engineering Education Graduates - Fendi Achmad; Nur Kholis; Roswina Dianawati; Daeng Rahmatullah; Yuli Sutoto Nugroho; Rizki Fitri Rahima Uulaa (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research aims to analyze (1) the direct influence of industrial work practice experience on work motivation, (2) the direct influence of industrial work practice experience on competency, (3) the indirect influence of industrial work practice experience on work readiness through work motivation; (4) the direct influence of career information on work motivation; (5) the direct influence of career information on competency; (6) indirect influence of career information on competence through work motivation; and (7) the direct influence of work motivation on the competency of undergraduate Electrical Engineering Education students at the Faculty of Engineering. Method: The quantitative approach used in this research is the path analysis model. The population in this study were all undergraduate students of Electrical Engineering Education at the Faculty of Engineering, with a total population of 194 graduate students. Results: This research concluded that (1) industrial work practice experience has a direct effect on work motivation by 16%; (2) industrial work practice experience has a direct effect on competency by 16.81%; (3) industrial work practice experience has an indirect effect on competence through work motivation of 1.25%; (4) career information has a direct effect on work motivation by 7.29%; and (5) career information has a direct effect on competency by 4.41%. Novelty: Internship experience has a direct influence on work motivation and competence. This means that the Department of Electrical Engineering is expected to properly monitor and evaluate the implementation of students' industrial work practices in industry. Monitoring can be done through monitoring instruments, which must be filled in by internal supervisors and external supervisors, with the hope of increasing the effectiveness of implementing industrial work practices. Apart from that, the industry is expected to be able to optimize the role of students during industrial work practices so that they gain knowledge and experience that influences work motivation and competence.